OPTIMALISASI PENGGUNAAN MEDIA DIGITAL DALAM PENINGKATAN KAPASITAS ANGGOTA KOPERASI - I Made Sudiksa; I Nyoman Sunarta; I Made Suidarma; Ketut Elly Sutrisni (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2025)
Cooperatives play an important role in supporting the people’s economy; however, most cooperative management in Bali remains conventional and has not yet fully utilized digital media. The purpose of this community service activity was to enhance the capacity of the management and members of the Kami Jaya Sejahtera Savings and Loans Cooperative (KSP), Denpasar, in utilizing digital media. The method used in this activity involved digital literacy training and hands-on practice in creating promotional content using simple applications. The evaluation results showed a significant increase in participants’ knowledge and skills, from an average of 15% on the pre-test to 85% on the post-test, with an average improvement of 83%. Participants were able to understand the benefits of social media for promotion, create educational content, and independently operate financial-recording applications. In addition to producing promotional content and a standard operating procedure (SOP) for the cooperative’s social media management, this activity also encouraged the implementation of more transparent and accountable digital financial record-keeping.